Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) berbantuan Pendekatan Investigasi terhadap Kemampuan Komunikasi Matematis - Rifa Fahrullisa; Fredi Ganda Putra; Nanang Supriadi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2018)
Mathematical communication ability of learners is still relatively low, this is allegedly caused by the conventional learning model that is still applied by educators. The authors in this study apply cooperative type model of TPS assisted investigative approach, because the type and approach is expected to be suitable to improve the mathematical communication ability of learners. The purpose of this research is to see the effect of Cooperative Learning Model Type Think Pair Share (TPS) assisted by an Investigation Approach to Mathematical Communication Ability. In this research including quantitative research because the data is processed in the form of numbers. Use experimental experimental quasy experiment type. To know the effect on the ability of mathematical communication owned peserta didiksetelah applied learning model is the purpose of the implementation of research. The instrument in this research is the test of mathematical communication ability on the matter of scale and comparison. Further data that have been obtained will be calculated by using Analysis of Variance (ANAVA) one unequal cell road. The result of this research is there is influence of thinking pair share learning model assisted by investigative approach to mathematical communication ability of learner, which in class which applied by model of learning pair help coupled with better investigation of mathematical communication ability compared with conventional learning model and TPS learning model.